Prevalence of Root-Knot Nematodes and Their Effects on Fruit Yield in Kiwifruit Orchards in Samsun Province (Türkiye) - Aydınlı, G.; Mennan, S. (Entomological Society of Turkey, 2022)
The aims of this study were to determine the distribution of root-knot nematodes (Meloidogyne spp.) in kiwifruit orchards in Samsun Province (Türkiye) and assess the effect of Meloidogyne spp. on fruit yields in naturally infested orchards. The survey was conducted in 25 kiwifruit orchards in September-November 2017. In addition, the data on fruit yields was obtained in two orchards at the harvest time in 2018. Fifty-six soil and root samples were collected from infested orchards. Species identification was performed by esterase phenotype and PCR with species-specific primers. Meloidogyne spp. were found in 92% of the orchards surveyed. Meloidogyne luci (Carneiro et al., 2014) (Tylenchida: Meloidogynidae) was detected in 59% of the samples, followed by Meloidogyne hapla (Chitwood, 1949) in 41%, Meloidogyne arenaria (Neal, 1889) in 27% and Meloidogyne incognita (Kofoid & White, 1919) in 2%. Regarding the distribution of Meloidogyne spp. in kiwifruit orchards, M. luci was found in 74%, M. hapla in 57%, M. arenaria in 39% and M. incognita in 4% of orchards infested. Meloidogyne luci was found for the first time in the kiwifruit orchards of Türkiye in this study. It was also determined that Meloidogyne spp. caused significant yield losses in kiwifruit orchards, and yield losses of 36 and 49% were detected in two orchards infested with Meloidogyne spp., respectively. © 2022 Entomological Society of Turkey. All rights reserved.
Samsun İli (Türkiye) Kivi Bahçelerindeki Kök-Ur Nematodlarının Yaygınlığı ve Meyve Verimine Etkileri
Keywords: Actinidia deliciosa; Distribution; Identification; Meloidogyne; Yield